The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.5296/jpag.v1i1.717
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Service Quality and Citizen Satisfaction in Southern Thailand

Abstract: The objectives of the research are two-folds: (1) to examine the quality of municipal services provided by local government in southern Thailand; and (2) to identify the most important service quality dimensions that determine citizen satisfaction. The questionnaires were distributed to 234 respondents in Tambon Khok Pho, a subdistrict of Khok Pho in Pattani Province of southern Thailand. Descriptive statistics, exploratory factor analysis, Pearson correlation and stepwise multiple regression were conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
2
17
1
2
Order By: Relevance
“…The result of this research study support the work of [49,61]. The authenticity of this research work is verified thoroughly, and the results vindicated that similar research come to agree with the conclusion of the results of this research work in many respects.…”
Section: Resultssupporting
confidence: 88%
“…The result of this research study support the work of [49,61]. The authenticity of this research work is verified thoroughly, and the results vindicated that similar research come to agree with the conclusion of the results of this research work in many respects.…”
Section: Resultssupporting
confidence: 88%
“…The result of this research study revealed that municipal council in Malaysia provide adequate and satisfactory services to their citizens, but need additional efforts as it was evident in the work of [29,59,58,51]. The authenticity of this research work is verified thoroughly, and the results vindicated that similar research come to agree with the conclusion of the results of this research work in many respects.…”
Section: Resultssupporting
confidence: 80%
“…The satisfaction of vulnerable group among the citizen in many municipal councils in Malaysia are giving more concerned as vindicated by [51]. But creation of awareness team within the municipal councils' staffs would be of help to the communities has revealed in [17].…”
Section: Resultsmentioning
confidence: 99%
“…Perceived service quality is defined by Zeithaml (1981) as "the judgment of the consumer as to the degree of excellence or superiority attributed to an entity". In this definition, service quality is the ability of an organization to meet or exceed consumer expectations (Mokhlis et al, 2011). This definition is part of the process of confirmation/disconfirmation of expectations as developed by Oliver (1980).…”
Section: Service Quality and Satisfaction With Local Authoritiesmentioning
confidence: 99%